2020
DOI: 10.1016/j.omtn.2019.11.027
|View full text |Cite
|
Sign up to set email alerts
|

LINC01413/hnRNP-K/ZEB1 Axis Accelerates Cell Proliferation and EMT in Colorectal Cancer via Inducing YAP1/TAZ1 Translocation

Abstract: Long non-coding RNAs (lncRNAs) are crucial molecules in tumorigenesis and tumor growth in various human cancers, including colorectal cancer (CRC). Studies have revealed that lncRNAs can regulate cellular processes in cancers by interacting with proteins, for example RNA-binding proteins (RBPs). In this study, we recognize a novel lncRNA called LINC01413 that is upregulated in CRC tissues through lncRNAs microarray. Subsequently, we confirmed that an elevated level of LINC01413 expression in CRC tissues was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…LncRNAs usually regulate target genes by interacting with RNA-binding proteins (RBPs). An increasing number of studies have identified the important roles of RBPs in regulating the lncRNAs and their downstream target genes [ 24 , 45 49 ]. We have identified hnRNPA1 as an interacting partner of H19 using RNA pull down and RIP assays.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs usually regulate target genes by interacting with RNA-binding proteins (RBPs). An increasing number of studies have identified the important roles of RBPs in regulating the lncRNAs and their downstream target genes [ 24 , 45 49 ]. We have identified hnRNPA1 as an interacting partner of H19 using RNA pull down and RIP assays.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs usually regulate target genes by interacting with RNA-binding proteins (RBPs). An increasing number of studies have identi ed the important roles of RBPs in regulating the lncRNAs and their downstream target genes (24,(45)(46)(47)(48)(49). We have identi ed hnRNPA1 as an interacting partner of H19 using RNA pull down and RIP assays.…”
Section: Discussionmentioning
confidence: 99%
“…c-Myc upregulated lncRNA (MYU) in colorectal cancer (CRC), was reported to directly interact with hnRNPK to stabilize the expression of cyclin-dependent kinase 6 (CDK6) (19). Several lncRNAs associated with hnRNPK including cancer susceptibility candidate 11 (CASC11) and Ets-1 promoter-associated noncoding RNA (pancEts-1) were reported to activate the Wnt pathway by stabilizing or activating b-catenin (20)(21)(22). Interaction of hnRNPK with LINC01413 increases the expression of ZEB1 by inducing the nuclear translocation of YAP1/TAZ1 (22).…”
Section: Discussionmentioning
confidence: 99%